Technology-based intervention programs to promote stimulation control and communication in post-coma persons with different levels of disability - Lancioni, Giulio E.; Bosco, Andrea; Olivetti Belardinelli, Marta; Singh, Nirbhay N.; O'Reilly, Mark F.; Sigafoos, Jeff; Oliva, Doretta (Frontiers in Human Neuroscience, 2014)
Post-coma persons in a minimally conscious state and with extensive motor impairment or emerging/emerged from such a state, but affected by lack of speech and motor impairment, tend to be passive and isolated. A way to help them develop functional responding to control environmental events and communication involves the use of intervention programs relying on assistive technology. This paper provides an overview of technology-based intervention programs for enabling the participants to (a) access brief periods of stimulation through one or two microswitches, (b) pursue stimulation and social contact through the combination of a microswitch and a sensor connected to a speech generating device (SGD) or through two SGD-related sensors, (c) control stimulation options through computer or radio systems and a microswitch, (d) communicate through modified messaging or telephone systems operated via microswitch, and (e) control combinations of leisure and communication options through computer systems operated via microswitch. Twenty-six studies, involving a total of 52 participants, were included in this paper. The intervention programs were carried out using single-subject methodology, and their outcomes were generally considered positive from the standpoint of the participants and their context. Practical implications of the programs are discussed.